Awareness of Lower Silesian residents of first aid procedures and the use of Automatic External Defibrillator (AED) device - Czarnecki, Mariusz; Sarnowska, Marta (Journal of Education, Health and Sport, 2018)
Recognizing the injured person and providing first aid is of key importance in the proper conduct of the survival chain. The aim of this study was to examine the awareness of Lower Silesian residents of first aid procedures and the use of Automatic External Defibrillator (AED) device. The study group consisted of 180 people of various ages, including 65 men and 115 women. 77 people from study group declared to have achieved higher education, 85 – average education, basic vocational education 10 and 8 – basic education For the needs of the study, an original, fully anonymous questionnaire was constructed and disseminated electronically through social media and discussion groups. The results of the survey showed, that the awareness of Lower Silesian residents about providing first aid and the usage of AED is not sufficient. Therefore, the first aid courses should address its important legal aspects, including issues related to the use of an AED.